Neuron and astrocyte specific 5mC and 5hmC signatures of BDNF’s receptor, TrkB - Wei, Xiaoran; Browning, Jack L.; Olsen, Michelle L. (Frontiers in Molecular Neuroscience, 2024)
Brain derived neurotrophic factor (BDNF) is the most studied trophic factor in the central nervous system (CNS), and its role in the maturation of neurons, including synapse development and maintenance has been investigated intensely for over three decades. The primary receptor for BDNF is the tropomyosin receptor kinase B (TrkB), which is broadly expressed as two primary isoforms in the brain; the full length TrkB (TrkB.FL) receptor, expressed mainly in neurons and the truncated TrkB (TrkB.T1) receptor. We recently demonstrated that TrkB.T1 is predominately expressed in astrocytes, and appears critical for astrocyte morphological maturation. Given the critical role of BDNF/TrkB pathway in healthy brain development and mature CNS function, we aimed to identify molecular underpinnings of cell-type specific expression of each TrkB isoform. Using Nanopore sequencing which enables direct, long read sequencing of native DNA, we profiled DNA methylation patterns of the entire TrkB gene, Ntrk2, in both neurons and astrocytes. Here, we identified robust differences in cell-type specific isoform expression associated with significantly different methylation patterns of the Ntrk2 gene in each cell type. Notably, astrocytes demonstrated lower 5mC methylation, and higher 5hmC across the entire gene when compared to neurons, including differentially methylated sites (DMSs) found in regions flanking the unique TrkB.T1 protein coding sequence (CDS). These data suggest DNA methylation patterns may provide instruction for isoform specific TrkB expression across unique CNS cell types.